Optimal organic carbon values for soil structure quality of arable soils. Does clay content matter? - Johannes, Alice; Matter, Adrien; Schulin, Rainer; Weisskopf, Peter; Baveye, Philippe C.; Boivin, Pascal (Geoderma, 2017)
Most soil structure-related physical properties are correlated to soil organic carbon (SOC) content. Texture, mineralogy, and SOC:clay ratio are also acknowledged to affect physical properties, however there is no consensus or general conclusions in this respect. Against this background, the present study aims at determining objectives for the management of SOC in terms of structural quality of agricultural soils. The large area in which 161 free-to-swell undisturbed samples were obtained for this research represents a major part of the Swiss agricultural land and belongs to one broad soil group (Cambi-Luvisols). The structural quality was scored visually, and bulk volumes (inverse of bulk density) were measured at standard matric potentials. To define the effect of SOC without interference of soil mechanical degradation, soils with good structural quality scores were considered first in studying the relationship between SOC and soil pore volumes. Results suggest that the relationship is always linear, irrespective of the clay content of the soils. No optimum of SOC corresponding to a fraction of the clay content is found, contrary to the theory of “complexed organic carbon” (Dexter et al., 2008). However, the SOC:clay ratio decreases with decreasing soil structure quality. The SOC:clay ratio of 1:8 is the average for a very good structure quality. A SOC:clay ratio of 1:10 is the limit between good and medium structural quality, thus it constitutes a reasonable goal for soil management by farmers. A SOC:clay ratio of 1:8 or smaller leads to a high probability of poor structural state. These ratios can be used as criteria for soil structural quality and SOC management, and in that context, the concept of complexed organic carbon appears relevant. •Total soil organic carbon controls physical properties•Complexed organic carbon concept is relevant for soil structure quality.•Reasonable goal in organic carbon for soil management is SOC:clay of 1:10.•Optimal value of organic carbon for soil structure quality is SOC:clay of 1:8.•Lower threshold of organic carbon for soil structure quality is SOC:clay of 1:13.